Severe Hemorrhagic Shock in a 93-Year Old Patient due to a Diagnostic Thoracocentesis Schwerer hämorrhagischer Schock bei einem 93-jährigen Patienten nach diagnostischer Pleurapunktion - Rupprecht, H.; Dormann, H.; Gaab, K. (Pneumologie, 2018)
An intercostal artery laceration is a rare iatrogenic complication following thoracocentesis and concerns especially elderly patients. We report a case of a severe hemorrhagic shock in a 93-year old patient due to diagnostic thoracocentesis.
CRIS-Team Scopus Importer:2025-02-03